2020
DOI: 10.21203/rs.3.rs-49168/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental Health Impacts for International Students During the COVID-19 Pandemic in China

Abstract: The outbreak of Coronavirus disease 2019 (COVID-19), has led to the quarantine of many residents in their homes worldwide. Some of these people might develop mental health problems, and many solutions have been put in place to address the mental health issues of patients and health professionals affected by the disease. However, not much attention has been given to international students studying in China. The present study aims to conduct an online survey to investigate the mental health status of internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…The cutoff points for a case finding are 10 for depression, 8 for anxiety, and 15 for stress. The depression subscale consists of items 3, 5, 10, 13, 16, 17, and 21 with scores ranging from normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), to extremely severe (28+). The anxiety subscale consists of items 2, 4, 7, 9, 15, 19, and 20, with scores ranging from normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), to extremely severe (20+).…”
Section: Depression Anxiety and Stress Scalesmentioning
confidence: 99%
See 3 more Smart Citations
“…The cutoff points for a case finding are 10 for depression, 8 for anxiety, and 15 for stress. The depression subscale consists of items 3, 5, 10, 13, 16, 17, and 21 with scores ranging from normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), to extremely severe (28+). The anxiety subscale consists of items 2, 4, 7, 9, 15, 19, and 20, with scores ranging from normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), to extremely severe (20+).…”
Section: Depression Anxiety and Stress Scalesmentioning
confidence: 99%
“…The anxiety subscale consists of items 2, 4, 7, 9, 15, 19, and 20, with scores ranging from normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), to extremely severe (20+). Finally, the stress subscale consists of items 1, 6, 8, 11, 12, 14, and 18, with scores ranging from normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33), to extremely severe (34+). The DASS-21 is a reliable, easy-to-use screening instrument and has been wellreceived globally.…”
Section: Depression Anxiety and Stress Scalesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reviewed research indicated significant incidence rates of psychological distresses amongst international students during the pandemic in association with different risk factors like gender, exposure to pandemic-related information, double-bind situation, sleep quality, and graduation uncertainty. [91][92][93] Amid the COVID-19 pandemic, university students' level of depression and anxiety was a prevailing research area with significant attention exhibited by interested researchers to assess the associations between specific covariates and these two psychological disorders.…”
Section: Discussionmentioning
confidence: 99%